AN ALTERNATIVE MODEL OF CHILD SEXUAL ABUSE HANDLING POLICY IN INDONESIA - Rd. Ahmad Buchari; Asep Sumaryana; Rosita Novi Andari (Universitas Padjadjaran, 2017)
Child sexual abuse is one of the forms of crimes against children that call for serious attention of the government. Indonesian Commission for Child Protection (KPAI)’s 2011-2016 years data shows that the number of child sexual abuse victims has been fluctuating year by year. The objectives of the present research were to evaluate the output of the implementation of government policies on handling child sexual abuses during 2011-2014, and to develop an alternative model of child sexual abuse handling policy suitable to apply in Indonesia. The research used a descriptive qualitative approach with a data collection technique of documentation and a descriptive data analysis. The research findings revealed that the policies currently pursued were generally ineffective both in prevention and in law enforcement against the offenders. Therefore, a model of child sexual abuse handling policy in Indonesia by a systems approach can be made as an alternative model of policies in dealing with the problem.